L’autoritratto o del vedersi vedere. Forme e retoriche di un non-genere letterario (Comparatismi, 2025)
While the self-portrait is a historically codified genre in the visual arts, its status within literature proves far more elusive. The recognition of the literary self-portrait as a distinct genre - defined by its own specific features and distinguishable from other forms of self-writing - can be traced back to the theoretical framework proposed by the French critic Michel Beaujour (1980), who situates its genealogy as far back as the medieval specula. Building on his reflections, this paper examines the interplay between textual form, visual dimension, and the author’s quest for identity. The analysis will focus on four texts, grouped according to their chronological and thematic affinities: Notturno by Gabriele D’Annunzio and L’Âge d’homme by Michel Leiris, Autoritratto automatico by Umberto Fiori, and Autoportrait by Éduard Levé.
Keywords: Self-Portrait; Autobiography; Genres; Identity; Writing